Vortex Formation in the Cardiovascular System - Kheradvar, Arash; Pedrizzetti, Gianni (Springer London : Imprint: Springer, 2012)
Vortex formation has received much attention over the past few years. Vortices occur in nature wherever propulsive flow exists; from erupting volcanoes to the ones generated by squid and jellyfish to propel them. There has been particular interest in the wide variety of vortices that develop in the cardiovascular system, particularly in the cardiac chambers and in large arteries. These vortices play fundamental roles in the normal physiology and provide proper balance between blood motion and stresses on the surrounding tissues. In contrast, formation of unnatural vortices may alter the momentum transfer in the blood flow and increase energy dissipation. Vortex Formation in the Cardiovascular System reviews the current knowledge of vortex formation, from the basic physics to cardiac physiology. There is a particular focus on the formation of vortices at different locations inside the heart, the effect of cardiac devices and surgery on vortex formation, fluid dynamics of the artificial heart valves and ventricular assist devices. The Authors have translated physical, mathematical and engineering concepts related to vortex formation into a clinical perspective with the objective to advance cardiovascular patient care. This book therefore represents a comprehensive and valuable resource for those involved in the field of cardiology and cardiovascular physiology, cardiovascular surgeons, interventional cardiologists, medical bioengineers and researchers in fluid mechanics.